Muscle-restricted knockout of connexin 43 and connexin 45 accelerates and improves locomotor recovery after contusion spinal cord injury - Toro, Carlos A.; De Gasperi, Rita; Vanselow, Katherine; Harlow, Lauren; Johnson, Kaitlin; Aslan, Abdurrahman; Bauman, William A.; Cardozo, Christopher P.; Graham, Zachary A. (Frontiers in Physiology, 2024)
Traumatic spinal cord injury (SCI) results in disruption of physiological systems below the level of spinal lesion. Connexin hemichannels (CxHC) are membrane-bound non-selective pore proteins that are lost with maturity but reappear de novo on the sarcolemma after peripheral denervation, chronic SCI, diabetes, and severe systemic stress such as sepsis. Cx43 and Cx45 have been implicated as the major CxHC present in diseased muscle and muscle-restricted knockout of these genes reduces muscle atrophy after denervation, likely by reducing excess calcium influx with resultant inflammasome activation. A muscle-restricted Cx43/45 conditional knockout (mKO) mouse was developed and tested whether it would improve outcomes following either a complete spinal cord transection at the level of thoracic vertebrae-9 (T9) or a motor-incomplete T9 impact-contusion SCI. mKO had no effect on body mass after complete T9 transection. There was reduced atrophy of the plantaris 15 d post-SCI that was not associated with molecular markers of inflammation, hypertrophic/atrophic protein signaling or protein and mRNA expression related to mitochondrial integrity and function. mKO mice had faster and greater locomotor recovery across 28 d after a motor-incomplete contusion SCI with no differences in spared white matter; male mKO mice generally had greater muscle mass than genotype controls post-injury, but muscle sparing was not in female mKO mice observed post-injury. The data establish a new paradigm wherein muscle Cx43/45 may contribute to the tissue crosstalk that determines neuromuscular function of sublesional musculature after motor-incomplete SCI in a manner that is dependent on gender. Our novel findings should stimulate investigation to develop innovative treatment strategies to improve function and quality of life for persons with SCI.